Effectiveness of ecommerce infrastructure towards purchase intention among STML Students in UUM - Nik Mahmud, Nik Nurul Amira; Othman, Abdul Aziz (Universiti Utara Malaysia, 2020)
Nowadays, the rapid growth of E-commerce infrastructure initiatives in the world reflects its compelling advantages and had increase drastically. This study attempts to evaluate the effectiveness of E-commerce infrastructure toward purchase intention among STML students in University Utara Malaysia (UUM). A survey was conducted from the administered questionnaire involves 100 respondents from STML students in UUM in which the data was collected directly from questionnaire survey with using the descriptive data of SPSS. Objective of this study are to measure the level of purchase intention of E-commerce infrastructure, to measure the relationship between convenience, customer satisfaction and information toward purchase intention. The findings indicate that convenience and information of use have significant affect toward purchase intention. However, it is found that there is no significant relationship between customer satisfaction and purchase intention.